Biochemical Constituents Influencing the Resistance to Flower Bud Thrips in Cowpea [Vigna Unguiculata (L.) Walp] Germplasm - Agbahoungba, S.; Karungi, J.; Odong, T.L.; Badji, A.; Kumi, F.; Mwila, N.; Rubaihayo, P.R. (The Journal of Animal & Plant Sciences, 2018)
The flower bud thrips, Megalurothrips sjostedti, is a major pest of cowpea that can cause yield losses of up to 100%. The use of cowpea cultivars resistant to thrips is among the most promising control measures. Six cultivars were evaluated in 2016 in Uganda for resistance to thrips under field conditions and analyzed for total carbon, total reducing sugar, total protein, soluble amino acid, total phenol, flavonoids, antioxidant activity and tannin contents. Data were subjected to analysis of variance, correlation and multiple linear regression analyses. The results showed that the genotypes responded differently to thrips damage and thrips counts in flowers and they presented different concentrations in total reducing sugar, total carbon, soluble amino acid, antioxidant activity, flavonoids and tannin in the plants parts. Cultivar TVU-1509 suffered the least thrips damage (1.03) while WC36 was severely damaged by thrips (6.55). A significant negative correlation was observed between thrips damage scores and total carbon concentration (r=-0.54) indicating that total carbon plays a significant role against thrips damage in cowpea. Increase in the concentration of flavonoids, total reducing sugar, total carbon in the plants contributed to the reduction of thrips damage (coefficient of regression = -1.47; -0.61 and -0.48, respectively) while the increase in the concentration of the soluble amino acid contributed to the increase of thrips damage (coefficient of regression = 2.10), suggesting that these biochemical conferred the resistance of cowpea to flower thrips damage. These biochemical compounds could be promising candidates to bolster cowpea cultivars ’resistance.
Keywords: Cowpea; Flavonoids; Megalurothrips sjostedti; Reducing sugar; Total carbon; Soluble amino acid